Study on Flow Model and Flow Equation of Shale Gas Based on Microflow Mechanism. (20th September 2022) - Liu, Huaxun; Gao, Shusheng; Fang, Feifei; Jiao, Chunyan; Ye, Liyou; Zhang, Jie; An, Weiguo
Abstract : Shale gas storage and permeability space is between nanometers and micrometers and has strong multiscale characteristics, resulting in highly complicated shale gas flow. Therefore, the development of shale gas needs to clarify the seepage mechanism of shale gas and establish a flow model and flow equation that can analyze shale gas flow. In this paper, based on the single nanotube model, combined with the Weiyuan-Changning shale gas demonstration zone of the target layer of the Longmaxi formation shale core high-pressure mercury pore throat test results, the contribution of seepage, diffusion, transition flow, and free molecular flow to shale gas flow was calculated. The contribution of seepage and diffusion is over 95%, and seepage and diffusion are the main flow pattern. Then, a shale gas seepage and diffusion coupled flow model and coupled flow equation were established. A method for calculating shale permeability and diffusion was proposed using the relationship between flow pressure and shale gas velocity. Finally, shale gas flow experiment analysis was carried out to verify that the established shale gas flow model and flow equation can describe the shale gas flow well. The result shows that the flow rate of shale gas is composed of seepage flow rate and diffusion flow rate. The seepage flow rate is proportional to the pseudopressure difference and proportionate to the low-pressure squared difference. The diffusion velocity is proportional to the difference in shale gas density, and the pressure difference in low pressure is proportional. As the pressure of a shale gas reservoir decreases, the proportion of diffusion flow increases. The research results enrich the understanding of shale gas flow; it also has particular reference significance to the development of shale gas reservoirs.